Russian Labour Market - Саймон Кларк (Journal of Economic Sociology, 2010)
The author starts the paper from the phrase: «The labour market was the only market in the Soviet Union, which could be called market in the capitalist economy», which is the background for the following discussion. The paper analyzes the distribution of the work force, entrance into the labour market, employment mobility, labour market policy and the meaning of perestroika for the labour market.